Public utility vehicle preferences and acceptance level for e-trikes a case study in Brgy Baldoza, Lapaz, Iloilo City - Comoro, Don Wade (University of the Philippines Visayas, 2013)
With the current threat of global warming, alternative renewable energies are being pushed through by different organizations throughout the world. It is believed that among the large contribution to the total greenhouse gas emission on earth is from smoke emission of combustion engine vehicles. With the advent of technology, alternative energy vehicles today are seen to be a valuable solution to this problem. However, just as any innovation it carries with it uncertainties on public cceptance. To assess this acceptability, this study aims to determine the public utility vehicle preferences by the residents of Brgy. Baldoza Lapaz, Iloilo City. Together with it s an analysis of the respondents' their level of acceptance for E-trikes, the factory they consider in choosing a public utility vehicle (PUV), as well as their awareness on alternative energy vehicles and its impacts to the environment. With these in consideration, this study also aims to determine if the repsondents to the environment. With these in consideration, this study also aims to determine if the respondents are willing to ride an E-trike and replace the conventional tricycle as a PUV. This study utilized survey method to gather primary data and used online resources for the secondary data. Frequency counts and percenatge as well as central tendencies were used to analyze the data. There were a total of 62 respondents considered in the survey. The results show that jeepneys are the most preferred land transportation vehicle followed by tricycle, pedicab, taxi and van respectively. Affordability is the most considered factor by the respondents in choosing a PUV. Also it is revealed that most of the residents are aware of the impacts of using alternative energy vehicles to the nevironement and most of them are willing to ride an E-trikes and replace the conventional tricycle as a PUV.